2020
DOI: 10.1021/acs.jmedchem.9b01913
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Stabilization of Non-native Protein–Protein Interactions of Coronavirus Nucleocapsid Proteins in Antiviral Drug Design

Abstract: Structure-based stabilization of protein−protein interactions (PPIs) is a promising strategy for drug discovery. However, this approach has mainly focused on the stabilization of native PPIs, and non-native PPIs have received little consideration. Here, we identified a non-native interaction interface on the three-dimensional dimeric structure of the N-terminal domain of the MERS-CoV nucleocapsid protein (MERS-CoV N-NTD). The interface formed a conserved hydrophobic cavity suitable for targeted drug screening.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 52 publications
3
94
0
2
Order By: Relevance
“…These two sites are shown in Sup. Figure 1E, F. Naproxen stabilized this "non -natural" interface as found in the crystal structure for the designed ligands by Hou et al 13 Figure 1H, E indeed show that naproxen can also bind at this interface in both MERS-CoV and SARS-Cov-2, respectively, but an additional binding site in SARS-CoV-2 monomer was also identified (Sup. Figure 1F).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…These two sites are shown in Sup. Figure 1E, F. Naproxen stabilized this "non -natural" interface as found in the crystal structure for the designed ligands by Hou et al 13 Figure 1H, E indeed show that naproxen can also bind at this interface in both MERS-CoV and SARS-Cov-2, respectively, but an additional binding site in SARS-CoV-2 monomer was also identified (Sup. Figure 1F).…”
supporting
confidence: 64%
“…Naproxen binding to the Influenza A virus nucleoprotein blocked viral RNA association with the nucleoprotein and impeded its self-association 6,9 ; consequently, naproxen strongly reduced viral transcription/ replication in infected cells and protected mice against an infection with Influenza A virus 6,10 . Viral nucleoproteins are unique to the virus and no equivalent of these proteins are found in the host cell, which makes them attractive targets for potential antivirals [12][13] . Moreover, the viral nucleoprotein is an important diagnostic marker of infection with SARS-COV and /or Influenza A [14][15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray studies were also performed on the identified compounds. Compound 139 blocks MERS‐CoV activity most likely prompting abnormal aggregation of the N protein within the cell . Targeting non‐native PPIs may represent a valuable approach to be possibly extended to SARS‐CoV‐2.…”
Section: Potential Therapeutic Strategies For Sars‐cov‐2mentioning
confidence: 99%
“…However, the structural and mechanistic basis for newly emerged novel SARS-CoV-2 N protein remain largely unknown. Understanding these aspects should facilitate the discovery of agents that specifically block the coronavirus replication, transcription and viral assembly 30 .…”
Section: Introductionmentioning
confidence: 99%